Examining a cavitation heat generator and the control method over the efficiency of its operation - Ved, Viktor; Nikolsky, Valeriy; Oliynyk, Olga; Lipeev, Alexander (Eastern-European Journal of Enterprise Technologies, 2017)
The cavitation heat generator for decentralized heating of industrial buildings and facilities was examined and implemented for actual operation. On this basis, a thermal system for decentralized heating of buildings was designed and studied. The circuit of the thermal system differs by the following feature: two connected cavitation heat generators are connected in series for heating of the liquid. At the same time, the heated liquid passes through a heat generator operating at high frequency, then through a heat generator operating at lower frequency. In the generator with high frequency, smaller cavitation embryos are excited, which increase in size in the generator with low frequency. This leads to increased impulses of cavitation pressure and increases the effect of cavitation. On this basis, a heat system for decentralized heating of buildings was designed, and studied, with its energy efficiency. To increase energy efficiency of the thermal system with cavitation heat generators, their sequential installation was proposed. The heated liquid must pass successively through a heat generator operating at high frequency, then through a heat generator operating at lower frequency. The efficiency of the system developed exceeds 18 % compared to the system of centralized heating by natural gas, which is a convincing prospect of use. A method for effective control over the cavitation process during operation of a heat generator was developed, based on the suppression of waves of oscillatory energy of the object. The method is based on direct measurements of vibrations – a parameter characterizing the process of cavitation. Approbation of the method for control over effectiveness of the cavitation process was carried out by measuring the vibrations at various temperatures of liquid at the outlet.